1995
DOI: 10.1128/mcb.15.12.6632
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the Self-Glucosylating Initiator Proteins Glg1p and Glg2p for Glycogen Accumulation in Saccharomyces cerevisiae

Abstract: Glycogen, a branched polymer of glucose, is a storage molecule whose accumulation is under rigorous nutritional control in many cells. We report the identification of two Saccharomyces cerevisiae genes, GLG1 and GLG2, whose products are implicated in the biogenesis of glycogen. These genes encode self-glucosylating proteins that in vitro can act as primers for the elongation reaction catalyzed by glycogen synthase. Over a region of 258 residues, the Glg proteins have 55% sequence identity to each other and ϳ33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
88
0
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 43 publications
3
88
0
1
Order By: Relevance
“…6). In the Glg proteins, the extreme COOH terminus may have a function in interactions with glycogen synthase (19,21). Glycogenin-2 has a Tyr in correspondence to rabbit muscle Tyr-194, the site of self-glucosylation, even though overall this is not a region of particularly high sequence conservation in different glycogenin and glycogenin-like proteins (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). In the Glg proteins, the extreme COOH terminus may have a function in interactions with glycogen synthase (19,21). Glycogenin-2 has a Tyr in correspondence to rabbit muscle Tyr-194, the site of self-glucosylation, even though overall this is not a region of particularly high sequence conservation in different glycogenin and glycogenin-like proteins (6).…”
Section: Discussionmentioning
confidence: 99%
“…6). Two self-glucosylating proteins, Glg1p and Glg2p, from the yeast Saccharomyces cerevisiae have been characterized and shown to be required for glycogen accumulation in that organism (19). In addition, searching GenBank revealed that Caenorhabditis elegans, Caenorhabditis briggsae, and Arabidopsis thaliana all express multiple glycogenin-like messages (6).…”
mentioning
confidence: 99%
“…It has been reported that disruption of both S. cerevisiae glycogenin-encoding genes completely abolished glycogen synthesis in the live yeast, thus indicating that S. cerevisiae GS is unable to initiate glycogen synthesis (13). An expression vector coding for S. cerevisiae GSII was introduced into A. tumefaciens A1120 strain, which lacks glycogen-branching enzyme, ADP-Glc pyrophosphorylase, and GS activities.…”
Section: S Cerevisiae Gs Expressed In a Tumefaciens Participates Inmentioning
confidence: 99%
“…We tested glycogen synthase II from S. cerevisiae (Gsy2p) as a reporter, which normally elongates (1,4)-␣-glucan primers generated by glycogenin, but lacks the ability to initiate de novo (1,4)-␣-glucan synthesis (33,40). Overexpression of wildtype S. cerevisiae Gsy2p in S. pombe cells resulted in a brown staining, whereas low expression did not (Fig.…”
Section: The Intracellular Domain Of Ags1p Is Responsible For (14)-␣mentioning
confidence: 99%